(untitled) (Global Journal of Sciences, 2024)
Chronic kidney disease (CKD) is a global health issue, predominantly caused by hypertension, which account for 80-85% of cases. CKD is categorized into five stages based on glomerular filtration rate (GFR), for its effective management a multidisciplinary approach that includes nutritional therapy is needed.As it is a slow progressing condition and to reduce the risks for cardiovascular risks accompanied by this, regular monitoring must be done. Regardless ofthe advances in the management of CKD, underprivileged population still face challenges in early detection and intervention to carry on. This case report focuses on a 42-year-old malepatient with CKD since 2 years and diagnosed with Hypertension since 10 yearswho received Ayurvedic treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi. A treatment comprising a blend of Panchakarma therapies and personalizedAyurvedic formulations is administered, resulting noticeable improvements in his symptoms, kidney function and overall well-being. After treatment, the patient showed considerable enhancements in GFR and reported relief from constipation and other symptoms. The serum urea and creatinine were also considerably regulated. This study results emphasis Ayurveda comparing to conventional treatment method as a potential cost effective therapy. These results highlight that Ayurveda can be cost-effective alternative for individuals who do not have access to advanced conventional healthcare. Even though the findings from this studies are promising, further studiesincluding larger randomized controlled trails is much needed to evaluate the efficiency and safety of these Ayurvedic interventions for CKD to standardize treatment protocols. Integrating the principles of Ayurveda with contemporary medical practices may provide a consolidated approach for the management of CKD, emphasizing the total well-being of the patien